The effect of special exercises using a designer device and added relative weights to develop some of the physical abilities of volleyball players - tariq, zeyad; Salih, Mohammed (Journal of Physical Education, 2022)
The aim of the study is to design an infrared device to determine the level of jumping, as well as to prepare special exercises using a device and added relative weights to develop some physical abilities of volleyball players, And the researcher used the experimental method, and the researcher adopted the work in the method of three equal groups (officer and experimentation) and conducting the tribal and remote tests, the research community was determined by volleyball players under (17) years of age in Baghdad, and the players were divided into three groups (officer and experiments), Each group consists of (5) players, and (3) players were excluded for their participation in the reconnaissance experiment, thus becoming the total number (15) players and reality (5) players , After presenting the results and analyzing them and discussing them and the researchers found that there were statistically significant moral differences between the three research groups, the researchers concluded that there was a change and improvement in the sample level of the two experimental groups of variables researched in the remote test after the application of the training units, and recommended the need to use the device by the trainers based on the research sample